Comparsion of the Effects of Succinate and NADH on Postmortem Metmyoglobin Redcutase Activity and Beef Colour Stability - Xiao-guang GAO; Zhen-yu WANG; Meng-tian TANG; Chang-wei MA; Rui-tong DAI (Journal of Integrative Agriculture, 2014)
In two experiments, the effects of succinate and NADH (reduced nicotinamide adenine dinucleotide) on metmyoglobin reductase activity and electron transport chain-linked metmyoglobin reduction were investigated and compared. In experiment 1, metmyoglobin (MetMb), substrate and inhibitors were incubated with mitochondria. Comparsion of the effects of succinate and NADH on MetMb reduction was investigated. The MetMb percentage in sample treated with 8 mol L−1 succinate decreased by about 69% after 3 h incubation, and the effect was inhibited by the addition of 10 mol L−1 electron transfer chain complex II inhibitor malonic acid; the MetMb percentage in samples treated with 2 mol L−1 NADH decreased by 56% and the effect was inhibited by the addition of 0.02 mol L−1 electron transport chain complex I inhibitor rotenone. These results indicated that electron transport chain played an important role in MetMb reduction. Both complex II and complex I take part in the MetMb reduction in mitochondria through different pathways. NADH-MetMb reduction system was less stable than succinate-MetMb system. In experiment 2, the beef longissimus dorsi muscle was blended with different concentrations of succinate or NADH. Enhancing patties with higher concentration of succinate or NADH improved colour stability in vacuum packaged samples (P<0.05). These results verified that mitochondria electron transport chain is related to the MetMb reduction in meat system.